Effectiveness of dairy products to protect against cognitive decline in later life: a narrative review - Anderson, Rachel C.; Alpass, Fiona M. (Frontiers in Nutrition, 2024)
As the world’s population ages the prevalence of age-related health concerns are is increasing, including neurodegeneration disorders such as mild cognitive impairment, vascular dementia and Alzheimer’s disease. Diet is a key modifiable risk factor for the development of neurodegeneration, likely due to gut-brain axis interactions related to neuroinflammation. Analyses of dietary patterns identified dairy as being part of a cognitively healthy diet; however, its contribution to cognitive outcomes is difficult to discern. This narrative review evaluates the literature to determine whether there is sufficient evidence that the consumption of dairy products helps to maintain cognitive function in later life. A search using the terms (dairy OR milk OR cheese OR yogurt OR yoghurt) AND (‘mild cognitive impairment’ OR dementia OR ‘Alzheimer's disease’) identified 796 articles. After screening and sorting, 23 observational studies and 6 intervention studies were identified. The results of the observational studies implied that the relationship between total dairy consumption and cognitive outcomes is inverse U-shaped, with moderate consumption (1-2 servings per day) being the most beneficial. The analysis of the intake of different types of dairy products indicated that fermented products, particularly cheese, were most likely responsible for the observed benefits. The experimental studies all used dairy-derived peptides produced during fermentation as the dietary intervention, and the results indicated that these could be an effective treatment for early-stage cognitive impairment. Further experimental studies with whole dairy products, particularly fermented dairy, are needed to determine whether the regular consumption of these foods should be recommended to maximise the likelihood of healthy cognitive ageing.